PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI ITWASDA POLDA PROVINSI PAPUA DENGAN MODERASI VARIABEL KOMPENSASI - Akbar, Rian; Fandiyanto, Randika; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of this study is to analyze the influence of variablesThe Influence of Organizational Culture and Motivation on the Performance of Itwasda Polda Papua Province Employees with Compensation Variable Moderation. Using the Partial Least Square (PLS) Structural Equation Model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Organizational culture has a significant positive effect on Employee Performance (H1 is accepted), Motivation has a significant positive effect on Employee Performance (H2 is accepted), Compensation is positive but not significant as a moderating variable of the influence of Organizational Culture on Performance (H3 is rejected). and Compensation is positive but not significant as a moderating variable of the influence of Motivation on Performance (H4 is rejected).